2006
DOI: 10.1287/moor.1050.0168
|View full text |Cite
|
Sign up to set email alerts
|

Bin Packing in Multiple Dimensions: Inapproximability Results and Approximation Schemes

Abstract: Abstract. We study the multidimensional generalization of the classical Bin Packing problem: Given a collection of d-dimensional rectangles of specified sizes, the goal is to pack them into the minimum number of unit cubes.A long history of results exists for this problem and its special cases. Currently, the best known approximation algorithm for packing two-dimensional rectangles achieves a guarantee of 1.69 in the asymptotic case (i.e., when the optimum uses a large number of bins) [3]. An important open qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
137
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(140 citation statements)
references
References 28 publications
0
137
0
3
Order By: Relevance
“…For the multi-dimensional case of packing hypercubes, there is an APTAS [4], and it is also shown that there exists an algorithm that packs (two-dimensional) rectangles into the optimal number of bins using resource augmentation. For the case of rectangles the currently best known result is a (1.405 + )-approximation [5].…”
Section: Other Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For the multi-dimensional case of packing hypercubes, there is an APTAS [4], and it is also shown that there exists an algorithm that packs (two-dimensional) rectangles into the optimal number of bins using resource augmentation. For the case of rectangles the currently best known result is a (1.405 + )-approximation [5].…”
Section: Other Related Workmentioning
confidence: 99%
“…There are many well-studied geometric problems in combinatorial optimization, for instance the natural geometric generalizations of fundamental one-dimensional problems like Knapsack or Bin Packing. For many settings of those, there are polynomial time algorithms known that give an approximation guarantee of 1 + , e.g., [13,4,9]. A common theme in these PTASs is the shifting technique: items that need to be packed are classified into large and small squares such that intuitively the large squares are much larger than the small ones.…”
mentioning
confidence: 99%
“…Bansal et al [2] devised a randomized algorithm with an asymptotic performance ratio of at most 1.525. As for the offline lower bound of the approximation ratio, Bansal et al [1] showed that the two-dimensional bin packing problem does not admit any asymptotic polynomial time approximation scheme.…”
Section: Related Workmentioning
confidence: 99%
“…These are the currently best-known approximation ratios for these problems. For packing squares into square bins, Bansal, Correa, Kenyon & Sviridenko [2] gave an asymptotic PTAS. On the other hand, the same paper showed the APXhardness of rectangle packing without rotations, thus no asymptotic PTAS exists unless P = N P. Chlebík & Chlebíková [4] were the first to give explicit lower bounds of 1 + 1/3792 and 1 + 1/2196 on the asymptotic approximability of rectangle packing with and without rotations, respectively.…”
Section: Introductionmentioning
confidence: 99%